2021
DOI: 10.1126/sciimmunol.abh3768
|View full text |Cite
|
Sign up to set email alerts
|

Integrated single-cell transcriptomics and epigenomics reveals strong germinal center–associated etiology of autoimmune risk loci

Abstract: Single-cell ATAC sequencing maps the cell type–specific regulatory potential of transcription factors and autoimmune disease risk loci.

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
27
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 36 publications
(28 citation statements)
references
References 82 publications
1
27
0
Order By: Relevance
“…Interestingly, a spatial expression correlation analysis revealed that the PC region contained distinct IgM/D and IgG/A areas (Figure S7G). Taken together, single-cell and ST results suggest that early PC differentiation in the tonsil consists of more subpopulations and states than previously appreciated (King et al, 2021b(King et al, , 2021a, being the primary reaction from follicular LZ-GCBCs associated with a stepwise progression towards mature PCs, and the extrafollicular secondary reaction from MBCs being a far more direct and rapid differentiation path into mature PCs.…”
Section: Plasma Cell Differentiation and Cell Identity Regulation In ...mentioning
confidence: 57%
See 1 more Smart Citation
“…Interestingly, a spatial expression correlation analysis revealed that the PC region contained distinct IgM/D and IgG/A areas (Figure S7G). Taken together, single-cell and ST results suggest that early PC differentiation in the tonsil consists of more subpopulations and states than previously appreciated (King et al, 2021b(King et al, , 2021a, being the primary reaction from follicular LZ-GCBCs associated with a stepwise progression towards mature PCs, and the extrafollicular secondary reaction from MBCs being a far more direct and rapid differentiation path into mature PCs.…”
Section: Plasma Cell Differentiation and Cell Identity Regulation In ...mentioning
confidence: 57%
“…Together, such complementary modalities contribute multiple layers to define cell identities (Wagner et al, 2016). Previous single-cell profiling efforts of the human tonsil already provided insights into specific cell populations (e.g., B cells (King et al, 2021b(King et al, , 2021a or innate lymphoid cells, ILCs (Björklund et al, 2016)), but lacked cell numbers and multimodal information to fully capture the cellular complexity of the organ. Here, we generated a human tonsil atlas composed of >357,000 cells profiled across five different data modalities, such as transcriptome, epigenome, proteome, adaptive immune repertoire and spatial location.…”
Section: Introductionmentioning
confidence: 99%
“…Our supposition is reinforced by work in germ-free pigs, where small-intestinal non-naive T and B cell abundances are reduced in the absence of microbial exposure (Rothk ötter & Pabst, 1989;Rothk ötter et al, 1994;Barman et al, 1996;Haverson et al, 2007;Sinkora et al, 2011;Potockova et al, 2015). Differences in T/B cells from mucosal tissues versus blood are also observed in humans, where non-naive lymphocytes increase in abundance, and tissuespecific gene signatures for lymphocyte activation, tissue residency, and/or effector functions are observed for tonsillar B cells (Glass et al, 2020;King et al, 2021), lung-derived T cells (Szabo et al, 2019a), and intestinal T cells (Venema et al, 2019) compared with similar lymphocyte subsets in the periphery. Collectively, the aforementioned studies and our own work suggest mucosal sites (including the ileum) are locations for congregation of non-naive T/B cells transcriptionally distinct from T/B cells found in the periphery, likely due in large part to ongoing immune stimulation via microbial exposure and other context-dependent signals at mucosal surfaces.…”
Section: Discussionmentioning
confidence: 99%
“…Together, these techniques can reveal the activity of noncoding DNA elements identified by GWASs and have been used to interrogate risk variants for conditions such as Alzheimer disease, Parkinson disease, autism spectrum disorder, and autoimmunity. 7 9 …”
Section: Introductionmentioning
confidence: 99%